Long‐term survival and loss in expectancy of life in a population‐based cohort of 7114 patients with diffuse large B‐cell lymphoma. Issue 8 (20th June 2018) - Ekberg, Sara; Jerkeman, Mats; Andersson, Per‐Ola; Enblad, Gunilla; Wahlin, Björn E; Hasselblom, Sverker; Andersson, Therese M.; Eloranta, Sandra; Smedby, Karin E.
Abstract: Survival has improved among patients with diffuse large B‐cell lymphoma (DLBCL) with the addition of anti‐CD20 antibody therapy. We aimed to quantify trends and remaining loss in expectation of life (LEL) due to DLBCL at a national population‐based level. Patients diagnosed with DLBCL 2000‐2013 ( N  = 7114) were identified through the Swedish Lymphoma Registry and classified according to the age‐adjusted International Prognostic Index (aaIPI). The novel measure LEL is the difference between remaining life years among patients and the general population and was predicted using flexible parametric models from diagnosis and among 2‐year survivors, by age and sex. Median age at DLBCL‐diagnosis was 70 (18‐105) years and 54.8% presented with stage III‐IV disease. On average, LEL due to DLBCL decreased from 8.0 (95% CI: 7.7‐8.3) to 4.6 (95% CI: 4.5‐4.6) years over the study period. By risk group, LEL was most reduced among patients with aaIPI ≥2 aged 50‐60 years. However, these patients were still estimated to lose >8 years in 2013 (eg, LELmales50years 8.6 years (95% CI: 5.0‐12.3)). Among 2‐year survivors, LEL was reduced from 6.1 years (95% CI: 5.6‐6.5) (aaIPI ≥ 2) and 3.8 years (95% CI: 3.6‐4.1) (aaIPI < 2) to 1.1 (95% CI: 1.1‐1.2) and 1.0 year (95% CI: 0.8‐1.1), respectively. The reduction was observed across all ages. Results for females were similar. By using LEL we illustrate the improvement of DLBCL survival over time. Despite adequate immunochemotherapy, substantial LEL among patients with IPI ≥ 2 points to remaining unmet medical needs. We speculate that observed reduced losses among 2‐year survivors indicate a reduction of late relapses.